1768. Efficacy and Safety of Switching From Boosted-Protease Inhibitors (bPI) Plus Emtricitabine/Tenofovir Disoproxil Fumarate (F/TDF) Regimens to the Once Daily (QD), Single-Tablet Regimen (STR) of Darunavir/Cobicistat/Emtricitabine/Tenofovir Alafenamide (D/C/F/TAF) in Virologically Suppressed, HIV-1-Infected Adults: Week 96 Results of the Phase 3, Randomized, Non-Inferiority EMERALD Trial. (26th November 2018) - Eron, Joseph; Orkin, Chloe; Cunningham, Douglas; Pulido, Federcio; Post, Frank; De Wit, Stéphane; Lathouwers, Erkki; Hufkens, Veerle; Petrovic, Romana; Van Landuyt, Erika; ,
Abstract: Background: The QD STR D/C/F/TAF 800/150/200/10 mg was noninferior to bPI + F/TDF at 48 weeks in EMERALD. Efficacy and safety of D/C/F/TAF through week 96 are presented. Methods: EMERALD (NCT02269917) is a randomized, active-controlled, open-label, international, multicenter noninferiority trial. Virologically suppressed (VL<50 c/mL for ≥2 months) ART experienced (previous non-DRV VF allowed) HIV-1-infected adults were randomized (2:1) to switch to D/C/F/TAF or continue bPI + F/TDF over 48 weeks. Patients could then continue on D/C/F/TAF or switch from bPI + F/TDF to D/C/F/TAF at week 52 (Late switch, 44 weeks D/C/F/TAF exposure) in a single-arm extension phase until week 96. The percentage of patients with virologic rebound (confirmed VL ≥50 c/mL) cumulative through week 48 and week 96 were primary and secondary endpoints, respectively. Results: Of 1141 randomized and treated patients (58% had received ≥5 previous ARVs including screening ARVs; 15% had previous non-DRV VF), 1, 080 continued in the extension phase ( N = 728 D/C/F/TAF; N = 352 late switch). Few patients had virologic rebound cumulative through week 96 in the D/C/F/TAF arm (3.1%, 24/763). Virologic rebound occurred in 2.3% (8/352) in the late switch arm over 44 weeks D/C/F/TAF treatment. Many rebounders (14/24 and 2/8) resuppressed by week 96. At week 96 a high percentage of patients in the D/C/F/TAF arm (90.7%, 692/763) were suppressed (VL<50 c/mL). In the late switch arm, 93.8% (330/352) maintained virologic suppression after 44 weeks of treatment. No DRV, primary PI, TFV, or FTC RAMs were seen post baseline. Few serious AEs and AE related discontinuations occurred in either arm (Table 1). Improvements in renal and bone parameters were maintained in the D/C/F/TAF arm and seen in the late switch arm (week 52–96), with a small change in TC/HDL-C ratio (Table 1). Conclusion: Switching to D/C/F/TAF maintained high virologic suppression rates (>90%) at week 96 with no resistance development, and was well tolerated over 96 weeks with bone, renal, and lipid safety consistent with known TAF and cobicistat profiles. Efficacy and safety results in the late switch arm were consistent with week 48 results in the D/C/F/TAF arm. D/C/F/TAF combines the efficacy and high genetic barrier to resistance of DRV with the safety benefits of TAF, even in patients with a history of non-DRV VF. Disclosures: J. Eron Jr., Gilead: Consultant and Grant Investigator, Consulting fee and Research grant. Janssen: Consultant, Consulting fee and Research grant. C. Orkin, AbbVie, Abbott, Boehringer Ingelheim, BMS, Gilead, GSK, Janssen, ViiV: Grant Investigator and Research Contractor, Research grant and Research support. D. Cunningham, Janssen: Investigator, Research grant. Gilead: Investigator, Research grant. F. Pulido, Janssen: Consultant, Investigator and Scientific Advisor, Consulting fee, Research support and Speaker honorarium. F. Post, Gilead: Consultant and Grant Investigator, Consulting fee and Grant recipient. Viiv: Grant Investigator, Grant recipient. Janssen: Consultant, Consulting fee. MSD: Consultant, Consulting fee. S. De Wit, Janssen: Investigator, Research grant. E. Lathouwers, Janssen: Employee and Shareholder, Salary. V. Hufkens, Janssen: Employee and Shareholder, Salary. R. Petrovic, Janssen R&D: Independent Contractor, Consulting fee. E. Van Landuyt, Janssen: Employee and Shareholder, Salary.